2020
DOI: 10.1038/s41467-020-16336-z
|View full text |Cite
|
Sign up to set email alerts
|

Black indium oxide a photothermal CO2 hydrogenation catalyst

Abstract: Nanostructured forms of stoichiometric In 2 O 3 are proving to be efficacious catalysts for the gas-phase hydrogenation of CO 2. These conversions can be facilitated using either heat or light; however, until now, the limited optical absorption intensity evidenced by the pale-yellow color of In 2 O 3 has prevented the use of both together. To take advantage of the heat and light content of solar energy, it would be advantageous to make indium oxide black. Herein, we present a synthetic route to tune the color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
191
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(197 citation statements)
references
References 39 publications
3
191
0
3
Order By: Relevance
“…30,[293][294][295] An appealing precedent of this approach was recently reported by Ozin and co-workers in the photo-thermal hydrogenation of CO 2 using the non-stoichiometric black In 2 O 3Àx /In 2 O 3 catalyst. 46 The authors found that the hydrogenation of pale yellow In 2 O 3 at different temperatures led to the generation of black nonstoichiometric heterostructures composed of In 2 O 3Àx domains in crystalline stoichiometric In 2 O 3 . These heterostructures displayed a broad absorption across the entire solar spectrum that provided an excellent photo-thermal performance.…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…30,[293][294][295] An appealing precedent of this approach was recently reported by Ozin and co-workers in the photo-thermal hydrogenation of CO 2 using the non-stoichiometric black In 2 O 3Àx /In 2 O 3 catalyst. 46 The authors found that the hydrogenation of pale yellow In 2 O 3 at different temperatures led to the generation of black nonstoichiometric heterostructures composed of In 2 O 3Àx domains in crystalline stoichiometric In 2 O 3 . These heterostructures displayed a broad absorption across the entire solar spectrum that provided an excellent photo-thermal performance.…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…[ 56 ] Another follow‐up study with respect to the non‐stoichiometric degree control of In 2 O 3− x /In 2 O 3 heterostructure in RWGS has unveiled that the photothermal hydrogenation of CO 2 was well equipped with both thermochemical and photochemical catalysis under the photogenerated heat and electrons, respectively. [ 57 ] The transcendent light absorption capacity of photocatalysts, especially in the near‐infrared (IR) region, can also be observed in defect‐induced LSPR features. [ 58 ] The introduction of oxygen vacancies provides excessive free electrons on the surface, thus leading to the LSPR in Bi 2 O 3− x and MoO 3− x nanosheets.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…Indium‐based materials is a promising candidate for photothermal catalysis of CO 2 hydrogenation 65‐70 . Ozin and coworkers reported that the defect‐laden In 2 O 3 − x (OH) y nanorod superstructures could be utilized as photothermal catalysts (Figure 2A) for efficient CO 2 hydrogenation toward CH 3 OH in a flow reactor 71,72 .…”
Section: Light‐driven Co2 Conversion Toward Methanolmentioning
confidence: 99%
“…Owing to the relatively limited utilization of the solar spectrum range over the pale‐yellow In 2 O 3 , the black In 2 O 3‐x that could utilize the full spectrum of the solar light has been successfully prepared. The resulting black In 2 O 3‐x exhibits more than 2400 times higher catalytic performance than the ordinary pale‐yellow In 2 O 3 65 …”
Section: Light‐driven Co2 Conversion Toward Methanolmentioning
confidence: 99%